Framework for Interoperable and Distributed Extraction-Transformation-Loading (ETL) Based on Service Oriented Architecture - Awad, Mohammed M.I. (2012)
Extraction. Transformation and Loading (ETL) are the major functionalities in data warehouse (DW) solutions. Lack of component distribution and interoperability is a gap that leads to many problems in the ETL domain, which is due to tightly-coupled components in the current ETL framework. This research discusses how to distribute the Extraction, Transformation and Loading components so as to achieve distribution and interoperability of these ETL components. In addition, it shows how the ETL framework can be extended. To achieve that, Service Oriented Architecture (SOA) is adopted to address the mentioned missing features of distribution and interoperability by restructuring the current ETL framework. This research contributes towards the field of ETL by adding the distribution and inter- operability concepts to the ETL framework. This Ieads to contributions towards the area of data warehousing and business intelligence, because ETL is a core concept in this area. The Design Science Approach (DSA) and Scrum methodologies were adopted for achieving the research goals. The integration of DSA and Scrum provides the suitable methods for achieving the research objectives. The new ETL framework is realized by developing and testing a prototype that is based on the new ETL framework. This prototype is successfully evaluated using three case studies that are conducted using the data and tools of three different organizations. These organizations use data warehouse solutions for the purpose of generating statistical reports that help their top management to take decisions. Results of the case studies show that distribution and interoperability can be achieved by using the new ETL framework.